Domestic Implementation of International Law in Indonesia and Thailand - Kusniati, Retno; Aekaputra, Prasit; Pitpiboonpreeya, Nhonlaphat (UI Scholars Hub, 2024)
This study aimed to examine the challenges related to domestic implementation of international law by comparing practices in Indonesia and Thailand. When both countries participated as State Parties to international treaties, this participation had legal consequences not only in the relationship with other states but also in implementing obligations under the relevant treaties through a transformation process governed by the Constitutions. Although most countries regulate the transformation of international treaties within the constitutions, Indonesia does not have the provisions. In contrast, Article 178 of the Thai Constitution provided a process for transforming international treaties into Thailand domestic law despite certain clauses of the article containing ambiguities that could require amendments to clarify the scope. To avoid uncertainties surrounding the validity of international treaties in domestic implementation, the first section of this study analyzed Indonesian and Thai practices in implementing law. The second section compared how the courts of both countries handled the positioning of international treaties. The final section provided recommendations for improving the integration of treaties into domestic law in both countries. In this context, constitutional amendments in both countries would be necessary. However, this decision would depend on the government’s awareness of national interests and could require further adjustments in the transformation process of treaties into domestic law.